Comparison of early postoperative recovery in patients undergoing elective colorectal surgery before and after ERAS® implementation—a single center three-armed cohort study: research - Knab, Katharina; Aurnhammer, Leon; Büttner, Sylvia; Seyfried, Steffen; Herrle, Florian; Reißfelder, Christoph; Vassilev, Georgi; Hardt, Julia (International journal of colorectal disease, 2024)
Purpose This study examines the impact of enhanced recovery after surgery (ERAS®) on patient recovery after elective colorectal surgery. The innovative PostopQRS™ tool was used for the analysis of patient recovery. Methods This single-center study compares three cohorts: two retrospective cohorts before (A) and after (B) ERAS® implementation and a prospective cohort post-ERAS® implementation (C) using PostopQRS™. The present study was prospectively registered in the German Register of Clinical Trials (DRKS00026903). Results A total of 153 patients were included from June 2020 to February 2022. Significant differences were observed in bowel function, oral food intake, opioid use, and PONV (postoperative nausea and vomiting) occurrence. By the day of discharge, 98% in cohorts B and C had bowel movements or stoma output, compared to 66% in cohort A (p < 0.001). Solid food intake on POD1 was higher in cohorts B and C (p = 0.025), while opioid use was lower (p = 0.003 and p < 0.001). Cohort C showed 90% recovery on discharge. Conclusion This study demonstrates improved early mobility, reduced need for opioids, a higher rate of patients with solid food intake on POD1, and earlier bowel movement as well as excellent recovery following the colorectal ERAS® implementation.
Gesehen am 10.04.2025